1977
DOI: 10.1161/01.cir.56.6.901
|View full text |Cite
|
Sign up to set email alerts
|

Improved outcome for prehospital cardiopulmonary collapse with resuscitation by bystanders.

Abstract: Despite the development of trained mobile rescue squads, cardiopulmonary collapse outside the hospital continues to carry a poor prognosis. We examined retrospectively the clinical courses of 19 consecutive coronary unit patients who had experienced prehospital cardiopulmonary resuscitation. Seven patients received basic life support from bystanders within five minutes. Cardiopulmonary resuscitation in the other 12 patients was delayed beyond five minutes pending the arrival of rescue personnel. Six of seven e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1982
1982
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…Two patients died of an unknown etiology. A multivariate model generated from all admission variables, including call-to-shock time (a consistent predictor of outcome [2, 3, 4, 5, 6, 7, 8, 9, 10]), reveals that digoxin use (HR 3.02, 95% CI 1.80–5.06, p < 0.001), hypertension (HR 2.06, 95% CI 2.123–3.45, p = 0.006), and call-to-shock time (HR 1.18, 95% CI 1.01–1.38, p = 0.038) were multivariate predictors of long-term mortality (fig. 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two patients died of an unknown etiology. A multivariate model generated from all admission variables, including call-to-shock time (a consistent predictor of outcome [2, 3, 4, 5, 6, 7, 8, 9, 10]), reveals that digoxin use (HR 3.02, 95% CI 1.80–5.06, p < 0.001), hypertension (HR 2.06, 95% CI 2.123–3.45, p = 0.006), and call-to-shock time (HR 1.18, 95% CI 1.01–1.38, p = 0.038) were multivariate predictors of long-term mortality (fig. 2).…”
Section: Resultsmentioning
confidence: 99%
“…This includes rapid access to emergency medical care, cardiopulmonary resuscitation, defibrillation and advanced care interventions [3]. Several studies have shown that rapid defibrillation after an OHCA in ventricular fibrillation (VF) is the single most important determinant of survival outcome [4, 5, 6, 7, 8, 9, 10]. Due to issues impeding the chain of survival, in most locations the survival rates range from 3 to 10% [4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, pass-not yet passed decisions based on the standard format o f the A H A or the recording strip may be unnecessarily stringent concerning C P R performance procedures. For early activation o f the emergency medical service and rapid initiation of BLS, the effect on outcome is well demonstrated [2,3,[27][28][29], while evidence for the effect on survival of variability in performance of cardiac compression or ventilation is not substantial. Lund [2] demonstrated a negative effect on survival of gross omissions in C P R technique (e.g.…”
Section: Consistency In Ranking 4 Discussionmentioning
confidence: 99%
“…Many reports provide data to compare the survival rates of cardiac arrest victims who receive "early" CPR (defined here as CPR initiated by citizens or bystanders) with the survival rates of those who receive "late" CPR (that CPR initiated by emergency responders) (22,25,27,38,46,52,53,64,66,89,90,95,97,(101)(102)(103)112). "Early" usually differs from "late" CPR by about four minutes.…”
Section: The Early Cpr Linkmentioning
confidence: 99%